Minimally Invasive Breast Fibroadenoma Excision Using an Ultrasound-Guided Vacuum-Assisted Biopsy Device - Papathemelis, Thomas; Heim, Stefanie; Lux, Michael P.; Erhardt, Ines; Scharl, Anton; Scharl, Sophia (Geburtshilfe und Frauenheilkunde, 2017)
Introduction We studied the extent to which an ultrasound-guided vacuum-assisted biopsy device ("hand-held Mammotome") could be used not only as a valuable tool for investigation of suspicious breast lesions, but also therapeutically for the complete removal of breast fibroadenomas. Materials and Methods 132 aspiration biopsies showing fibroadenoma on histology were collected retrospectively. We ascertained whether there were residual findings on breast ultrasound at a median follow-up of approx. 9 months following biopsy. A questionnaire was used to determine the complication rate, patient satisfaction and acceptance of the procedure. Results In this study complete fibroadenomectomy was achieved at aspiration biopsy in 76 % of cases (n = 132). Compared to fibroadenomas larger than 2.51 cm3 (59 %), those smaller than 2.5 cm3 were completely removed more often (87.6 %; p < 0.05). The procedure is associated with very little pain during and after biopsy and minimal haematoma development, both factors supporting a high rate of acceptance among patients. Conclusion Ultrasound-guided vacuum-assisted biopsy is safe and associated with very few complications. Its additional therapeutic potential is dependant on the size of the benign lesion as measured at initial ultrasound.
EVALuna2:36170